Assessment of the Influence of Cell Technologies on Denervation-Reinnervation Processes in Muscles after Gunshot Injury Using Shear Wave Elastography (SWE) - Dolhopolov, O.V.; Zinchenko, V.V.; Yarova, M.L.; Siforov, D.V.; Haiko, O. G.; Klymchuk, L.I.; Luchko, R.V. (TERRA ORTHOPAEDICA, 2023)
Objective. The purpose of this article is to determine the feasibility of using shear-wave elastography (SWE) in assessing the influence of cell technologies on denervation-reinnevaration processes in the muscles of gunshot injury.Material and Methods. Ultrasound examination and elastography were performed on a GE Healthcare LOGIQ P9 device with a 5-12 MHz multi-frequency probe. 19 injured males aged 35-57 (average age 45.31±0.95 years) with denervation-reinnervation processes in muscles due to gunshot damage were examined. The examination was performed on the affected limb and on the contralateral healthy limb. Statistical processing was performed using Microsoft Excel and StatSoft Inc. STATISTICA.Results: 11 patients with lesions of the radial nerve on the upper limb and 8 people of the peroneal nerve on the lower leg were included in the study. With lesions of the radial nerve, we examined m. extensor digitorum on the forearm. For lesions of the peroneal nerve, m. tibialis anterior of the lower leg was chosen. After the examination, all patients underwent the procedure of injecting BMAC (Bone Marrow Aspirate Concentrate) into the target muscle. Control studies of shear wave elastography were performed again one month after the procedure. The obtained statistical data on the state of muscle stiffness in dynamics allow us to conclude about the reliably positive outcome of the treatment.Conclusions. Ultrasound of muscles with shear wave elastography is a reliable and innovative method of obtaining information about the state of muscle stiffness when assessing the influence of cellular technologies on denervation-reinnervation processes in patients after gunshot injuries.